Enarodustat for the Treatment of Anemia in Chinese Patients with Non-Dialysis Chronic Kidney Disease: A Phase 3 Trial - Xin-Ling Liang; Ren-Wei Huang; Jian-Teng Xie; Yan-Ning Zhang; Yi-Nan Li; Xiao-Nong Chen; Tian-Jun Guan; Hua Zhou; Ping Fu; Yun-Hua Liao; Hui Xu; Ai-Cheng Yang; et al. (Kidney Diseases)
Introduction: Renal anemia is a common complication among patients with non-dialysis chronic kidney disease (ND-CKD), and there remains an unmet need for more efficient and convenient daily oral medications to improve patient outcomes. This study aimed to evaluate the efficacy and safety of enarodustat, a hypoxia-inducible factor-prolyl hydroxylase inhibitor, in treating anemia for ND-CKD patients. Methods: This phase 3 study was conducted at 48 centers across China, enrolling 156 ND-CKD patients. Participants were randomly randomized in a 2:1 ratio to receive either enarodustat or placebo for an initial 8-week double-blind period, followed by a 16-week open-label period during which all patients received enarodustat. Results: The primary endpoint was the mean change in hemoglobin (Hb) levels from baseline to the average level during weeks 7–9. Secondary endpoints focused on Hb concentration or treatment pattern, while exploratory endpoints assessed iron metabolism-related parameters. The mean (±SD) change in Hb levels from baseline to weeks 7–9 was 15.99 (±9.46) g/L in the enarodustat group, compared to -0.14 (±8.08) g/L in the placebo group, resulting in a mean difference of 16.00 (±1.54) g/L (p < 0.001). During weeks 7–9, 85.3% of patients in the enarodustat group achieved Hb levels =100 g/L with 86.0% maintaining this level during weeks 21–25. In the first 4 weeks, the Hb increased by 11.82 (±9.56) g/L in the enarodustat group. By week 9, the mean change in hepcidin level was -42.94 (±37.56) ng/mL in the enarodustat group, compared to +4.58 (±33.34) ng/mL in the placebo group. Enarodustat also improved other iron-related parameters and reduced the need for iron supplements. The safety profile of enarodustat was well tolerable with adverse events comparable to those of the placebo. Conclusion: Enarodustat effectively corrected renal anemia with a manageable safety profile. Its once-daily oral administration offers convenience that may enhance the adherence. Enarodustat shows the potential as a promising therapy for anemic patients with ND-CKD.